Multifaceted Impacts of Periodontal Pathogens in Disorders of the Intestinal Barrier - Liu, Yingman; Huang, Wenxuan; Wang, Jiaqi; Ma, Jiaojiao; Zhang, Manman; Lu, Xiaoying; Liu, Jie; Kou, Yurong (Frontiers in Immunology, 2021)
Periodontal disease, a common inflammatory disease, is considered a hazardous factor that contributes to the development of diseases of the digestive system as well as other systems. The bridge between periodontitis and systemic diseases is believed to be periodontal pathogens. The intestine, as part of the lower gastrointestinal tract, has a close connection with the oral cavity. Within the intestine, the intestinal barrier acts as a multifunctional system including microbial, mucous, physical and immune barrier. The intestinal barrier forms the body’s first line of defense against external pathogens; its breakdown can lead to pathological changes in the gut and other organs or systems. Reports in the literature have described how oral periodontal pathogens and pathobiont-reactive immune cells can transmigrate to the intestinal mucosa, causing the destruction of intestinal barrier homeostasis. Such findings might lead to novel ideas for investigating the relationship between periodontal disease and other systemic diseases. This review summarizes studies on the effects of periodontal pathogens on the intestinal barrier, which might contribute to understanding the link between periodontitis and gastrointestinal diseases.